Guidance counsellor-student interaction - Hakanpää, Linnea (2024)
This thesis explores the evolving landscape of guidance counsellor-student interactions within the context of general upper secondary education in Finland. With a focus on recent changes in the educational system, including the COVID-19 pandemic, extended compulsory education, and student admission reform, the study aims to understand how these changes intersect with guidance counsellor-student interactions. Through qualitative interviews with guidance counsellors, the study investigates their experiences, challenges, best practices, and future development ideas, employing a thematic analysis with an inductive-deductive approach.